Rising Illiberalism in the European Periphery and the Eu's Application of Membership Conditionality - Saatçioğlu, Beken (My University, 2018)
How consistently has the EU used membership conditionality to address illiberalism? Has it sufficiently and effectively used its conditional, transformative capacity in the first place, i.e., independent of the domestic factors gaining ground in third countries and paving the way for illiberalism? This paper proposes to assess this question by focusing on the EU’s recent relations with Turkey, as the longest standing EU candidate, within the context of the 2015 Syrian refugee crisis. This episode of EU-Turkey relations provides a real test case for the EU’s ability and willingness to consistently use conditionality since doing so coincided with the EU’s other foreign policy aims linked with external border security (relatedly also, the integrity of the Schengen area) and even, protection against terrorism.
Keywords: Turkey; Conditionality; European periphery; EU; Illiberalism